2008
DOI: 10.1007/s11738-008-0177-z
|View full text |Cite
|
Sign up to set email alerts
|

Responses of MxPPO overexpressing transgenic tall fescue plants to two diphenyl-ether herbicides, oxyfluorfen and acifluorfen

Abstract: We generated transgenic tall fescue (Festuca arundinacea Schreb. cv. Kentucky-31) plants harboring a synthetic Myxococcus xanthus protoporphyrinogen oxidase (MxPPO) gene through Agrobacterium-mediated gene transfer. Successful integration of the transgene into the genome of transgenic plants confirmed by polymerase chain reaction (PCR) and Southern blot analysis, and the functional expression of the MxPPO gene at the mRNA level in transgenic lines was validated by Northern blot analysis. Responses of transgeni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 51 publications
0
8
0
Order By: Relevance
“…Biotechnological approaches have the potential to complement or accelerate conventional breeding by extending the range of sources for valuable traits, thus offering new opportunities for tall fescue improvement. Indeed, the molecular breeding of tall fescue for tolerance to herbicides (Lee et al 2008), salt, and drought (Cao et al 2009;Zhao et al 2007) has been reported. The stress-inducible expression of two antioxidant genes (CuZnSOD and APX) simultaneously able transgenic plants to tolerate a wide range of abiotic stresses, including methyl viologen (MV), H 2 O 2 , and heavy metals (Lee et al 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Biotechnological approaches have the potential to complement or accelerate conventional breeding by extending the range of sources for valuable traits, thus offering new opportunities for tall fescue improvement. Indeed, the molecular breeding of tall fescue for tolerance to herbicides (Lee et al 2008), salt, and drought (Cao et al 2009;Zhao et al 2007) has been reported. The stress-inducible expression of two antioxidant genes (CuZnSOD and APX) simultaneously able transgenic plants to tolerate a wide range of abiotic stresses, including methyl viologen (MV), H 2 O 2 , and heavy metals (Lee et al 2007).…”
Section: Introductionmentioning
confidence: 99%
“…ELISA assays ELISA assays were used to quantify CP4-EPSPS protein, essentially as described previously [16]. Leaf samples from non-transgenic plants and independent transgenic lines were collected.…”
Section: Rna Isolation and Northern Blot Analysismentioning
confidence: 99%
“…Milli-Q water was used as a control. The treatment procedure was performed according to that described by Lee et al [16]. The plants were observed over 1 week to determine resistance or susceptibility to the herbicide.…”
Section: Analyses Of Herbicide Tolerancementioning
confidence: 99%
“…Chen et al (1977) and Chen and Boe (1988) The objective of this study was, therefore, to establish an efficient regeneration system from the calli of mature seeds in big bluestem cultivars, Kaw and Earl, that are well adapted to the southern US. Mature seeds are considered an important source of explants, as they are readily available and used frequently for in vitro regeneration (Li et al, 2009a;Lee et al, 2006Lee et al, , 2008.…”
Section: Introductionmentioning
confidence: 99%